INCIDENCE OF ORAL CANDIDIASIS IN FIXED ORTHODONTIC APPLIANCES - Wahyuni Dyah Parmasari; Masfufatun; Tri Juliati (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introductions: Oral candidiasis is most often caused by Candida albicans, followed by C. glabrata. In European countries, an analysis showed that more than half of candidiasis cases were caused by C. albicans and the infection rate caused by other candida strains was 14% for C. glabrata and C. parapsilosis, 7% for C. tropicalis and 2% for C. krusei. According to a study in Brazil, C. albicans accounted for 40.9% of cases followed by C. tropicalis (20.9%), C. parapsilosis (20.5%) and C. glabrata (4.9%). Meanwhile, in Indonesia, there is no national data regarding the epidemiology of oral candidiasis in Indonesia. Hospital Dr. Hasan Sadikin (RSHS) Bandung conducted research from 2010-2014 and found that during that period 49 patients had oral candidiasis. In general, side effects can be felt by patients who are in fixed orthodontic treatment which affects comfort and quality of life, namely 42.79% experience a sensation of pain in the area of the oral cavity, while 51.80% complain of discomfort when chewing food and this can indicate that Orthodontic appliances are mainly the patient's daily activities, the second is related to chewing food, phonetics and smile lines. The purpose of this study was to determine the incidence of candidiasis on orthodontic appliances. This study was to determine the incidence of candidiasis on fix orthodontic appliances. Material and Methods: In this study, 80 samples were obtained from the total population, namely medical students who use fixed orthodontics with metal materials. Methods with SWAB examination on the surface of the bracket and the oral mucosa that intersect with the ortho-adhesive device. The results were recorded and then data analysis was carried out. Then the specimens were put in a microbiology incubator for 48 hours at room temperature. If candida albicans grows on the petridish then it is assessed that candidiasis is present. Results: From the study, it was found that 80% incidence of candidiasis, 20% is normal. Conclussions: There is a high incidence of oral candidiasis in patients using fix orthodontics appliances.